2013
DOI: 10.1371/journal.pone.0075405
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Nuclear p300 Is Associated with Disease Progression and Worse Prognosis of Melanoma Patients

Abstract: BackgroundGenomic instability due to UV radiation is one of the leading causes for melanoma. Histone acetyltransferase p300 plays an indispensible role in DNA repair and maintenance of genomic integrity. The present study was performed to analyze the correlation between p300 expression, melanoma progression and patient survival.MethodsTissue microarray and immunohistochemical analysis was employed to study the expression of p300 in melanoma patients. A total of 358 melanoma patients (250 primary melanoma and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 37 publications
0
27
1
Order By: Relevance
“…Data from our previous study showed that though cytoplasmic p300 expression was significantly associated with clinico-pathologic characteristics of melanoma, only nuclear p300 had prognostic significance [10]. Even in the present study, cytoplasmic p300 expression was only informative during the diagnosis part of the analysis but was not a significant prognostic factor (Table  4).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Data from our previous study showed that though cytoplasmic p300 expression was significantly associated with clinico-pathologic characteristics of melanoma, only nuclear p300 had prognostic significance [10]. Even in the present study, cytoplasmic p300 expression was only informative during the diagnosis part of the analysis but was not a significant prognostic factor (Table  4).…”
Section: Discussioncontrasting
confidence: 63%
“…Furthermore, we also found that nuclear p300 expression was an independent prognostic factor, suggesting the importance of targeting the functions of histone acetyltransferases (HAT) in melanoma therapy [10]. Stability and activity of p300 protein have been shown to be regulated by phosphorylation, and phosphorylation of p300 by mitogen activated protein kinase (MAPK) and extracellular signal-regulated kinase (ERK1/2) has been reported to promote the degradation of p300 protein [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of melanoma tissue blocks and construction of tumor tissue microarrays have been described previously [6,7,12,[33][34][35][36][37]. The formalinfixed, paraffin embedded archival biopsies of benign melanocytic nevi, melanoma in situ, invasive primary melanoma and metastatic melanoma were obtained from the 1990 to 2009 archives from the Department of Pathology at Vancouver General Hospital, Vancouver, Canada.…”
Section: Immunohistochemistry (Ihc) Staining Of Tissue Microarraysmentioning
confidence: 99%
“…The clinicopathological data was available for all melanoma cases. EYA1 expression was analyzed by immunohistochemistry on paraffin-embedded tissue microarrays as described previously [6,7,12,[33][34][35][36][37]. Briefly, de-paraffinized 4μm tissue sections were treated 30 minutes in 0.1M sodium citrate (PH6.0) at 95˚C for antigen retrieval.…”
Section: Immunohistochemistry (Ihc) Staining Of Tissue Microarraysmentioning
confidence: 99%
See 1 more Smart Citation